Egg production in naked-neck Creole (Nana) hens and in those with normal plumage (nana) in the region of the Mexican plateau - Ju?rez-Caratachea, A.; Guti?rrez-V?zquez, Ernestina; Garcidue?as-Pi?a, R.; Salas-Razo, G. (Cuban Journal of Agricultural Science, 2010)
The egg production from naked neck Creole hens (Nana) and those with normal plumage (nana) was compared in the environmental conditions of the Mexican plateau, located in the central region of the Michoacan state. Ninety hens of 20 weeks of age were used, 45 of them were heterozygotic naked neck (Nana), and 45 were homozygotic with normal plumage (nana). The outcomes for a period of 10 months showed that the total egg production and the total egg mass were significantly higher (P < 0.05) in naked neck hens, compared with those of normal plumage (156 ? 6.93 vs 144 ? 5.92 eggs and 8.02 ? 0.36 vs 7.32 ? 0.31 kg, respectively). There were not significant differences in the weight of the hen when laying the first egg, the weight of the egg, the egg production per bird in cage, or in the eggshell quality. It was considered that, in the plateau conditions in the central area of the Michoacan state, the naked neck Creole hens (Nana) had better productive performance than those with normal plumage (nana), although they were similar as to the egg weight and the eggshell characteristics. Key words: naked neck gene, environmental temperature, Mexican plateau, egg production.